2021
DOI: 10.1007/s11548-021-02354-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marker position and size on the registration accuracy of HoloLens in a non-clinical setting with implications for high-precision surgical tasks

Abstract: Purpose Emerging holographic headsets can be used to register patient-specific virtual models obtained from medical scans with the patient’s body. Maximising accuracy of the virtual models’ inclination angle and position (ideally, ≤ 2° and ≤ 2 mm, respectively, as in currently approved navigation systems) is vital for this application to be useful. This study investigated the accuracy with which a holographic headset registers virtual models with real-world features based on the position and size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Considering that CFA puncture was performed repetitively on an immobile phantom model and in an experimental setting using an advanced navigation system, the results of this study demonstrate the necessity of further improvements in positional accuracy of the registration process before transfer of this technology into clinical practice can be suggested. Previous studies have demonstrated that the number, size, and position of the radiopaque markers may play an important role for accurate pattern recognition [34]. Other factors, such as calibration errors, are also known to have an influence on positional error and these sources of error should be subject to systematic investigation in the future [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that CFA puncture was performed repetitively on an immobile phantom model and in an experimental setting using an advanced navigation system, the results of this study demonstrate the necessity of further improvements in positional accuracy of the registration process before transfer of this technology into clinical practice can be suggested. Previous studies have demonstrated that the number, size, and position of the radiopaque markers may play an important role for accurate pattern recognition [34]. Other factors, such as calibration errors, are also known to have an influence on positional error and these sources of error should be subject to systematic investigation in the future [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the number, size, and position of the radiopaque markers may play an important role for accurate pattern recognition [34]. Other factors, such as calibration errors, are also known to have an influence on positional error and these sources of error should be subject to systematic investigation in the future [34,35]. Furthermore, not only could technological improvements advance the applicability of MR technology in surgical guidance, but also the use of creative synergies of existing technology.…”
Section: Discussionmentioning
confidence: 99%
“…Auch der Einsatz von MR-assistierter Navigation am Patienten wurde bereits beschrieben. Lu et al [24] [23,26,30]. Sollen anschließend in der MR-Umgebung ohne Einsatz von Röntgenstrahlung Katheter navigiert werden, so ist darüber hinaus ein Tracking der einzelnen zur Anwendung kommenden chirurgischen Instrumente notwendig.…”
Section: Informationsmanagement Und Ergonomieunclassified
“…Perez-Pachón et al, 2021 [10] investigated the effect of marker positioning and size on the registration accuracy of HoloLens in a non-clinical environment with applications for high-precision surgical tasks. In surgery, image-pattern-recognition tools recognize the images and compute registration using image markers.…”
Section: Background and Introductionmentioning
confidence: 99%